2017
DOI: 10.1074/jbc.m116.771030
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a missense mutation in the O-linked β-N-acetylglucosamine (O-GlcNAc) transferase gene that segregates with X-linked intellectual disability

Abstract: -GlcNAc is a regulatory post-translational modification of nucleocytoplasmic proteins that has been implicated in multiple biological processes, including transcription. In humans, single genes encode enzymes for its attachment (-GlcNAc transferase (OGT)) and removal (-GlcNAcase (OGA)). An X-chromosome exome screen identified a missense mutation, which encodes an amino acid in the tetratricopeptide repeat, in (759G>T (p.L254F)) that segregates with X-linked intellectual disability (XLID) in an affected family.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
137
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 69 publications
11
137
3
Order By: Relevance
“…B). This hints at the existence of a compensatory mechanism that allows cells to partially maintain O ‐GlcNAc homeostasis by reducing OGA levels—as also observed in some of the other OGT XLID mutations in the TPR domain . Thus, the N648Y mutation leads to hypoglycosylation in mES cells.…”
Section: Resultsmentioning
confidence: 71%
“…B). This hints at the existence of a compensatory mechanism that allows cells to partially maintain O ‐GlcNAc homeostasis by reducing OGA levels—as also observed in some of the other OGT XLID mutations in the TPR domain . Thus, the N648Y mutation leads to hypoglycosylation in mES cells.…”
Section: Resultsmentioning
confidence: 71%
“…To date, 7 different mutations in OGT have been found in 11 individuals with ID. Familial inheritance indicates that OGT mutations segregate with ID, providing further support for the involvement of OGT in ID [96][97][98].…”
Section: Huwe1 Mutations In Syndromic and Nonsyndromic Intellectual Dmentioning
confidence: 77%
“…OGT was found to function with EEL-1 to regulate inhibitory GABA neuron function. Similar to HUWE1, human genetic studies have identified OGT mutations in multiple families with non-syndromic ID [80,[95][96][97][98]. To date, 7 different mutations in OGT have been found in 11 individuals with ID.…”
Section: Huwe1 Mutations In Syndromic and Nonsyndromic Intellectual Dmentioning
confidence: 85%
“…The TPR region folds into a super α‐helix and has been suggested to play an important role in protein interactions . Furthermore, mutations in the TPR region have been implicated in intellectual disability . Three isoforms of human OGT have been reported, which differ only in the number of TPR repeats: 13.5 for ncOGT (the most abundant isoform in the nucleus and cytoplasm), nine for mOGT (mitochondria), and 2.5 for a short isoform, sOGT.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] Furthermore, mutationsi nt he TPR region have been implicated in intellectual disability. [29][30][31] Three isoformso fh uman OGT have been reported, [32,33] which differ only in the number of TPRr epeats:1 3.5 for ncOGT( the most abundant isoform in the nucleusand cytoplasm), nine for mOGT (mitochondria), and 2.5 for as hort isoform, sOGT.H owever,t he physiological importance of the two shorter isoforms remain mostly unknown. [34][35][36] Several studies have reported that the extended TPR region is necessary for binding and glycosylating protein-but not peptide-substrates.…”
Section: Introductionmentioning
confidence: 99%